Al-Baghdadi’s Usul al-Din: Analyzing Epistemological Themes - Ryandi, Ryandi; Drajat, Amroeni; Sukiman, Sukiman (Universitas Darussalam Gontor, 2025)
Al-BaghdÄdÄ« holds a significant position within the early Ashâ€˜ari epistemological tradition. His work, Usul al-DÄ«n, offers a systematic explanation of the foundational principles of Sunni belief, integrating an epistemological framework that draws from both the Ashâ€˜ari intellectual tradition and the broader Islamic intellectual heritage. This study employs qualitative textual analysis of Usul al-DÄ«n, focusing primarily on how Al-BaghdÄdÄ« articulates various epistemological concepts. Several themes are explored within the text, including the definition, classification, and sources of knowledge. The analysis reveals that Al-BaghdÄdÄ« places knowledge as the foundational principle in his theological discussions. Through his structured and profound approach, Al-BaghdÄdÄ« views epistemology as an essential tool for resolving theological issues, providing a rational foundation for understanding Islamic faith. This focus on epistemology not only lays the groundwork for the further development of Ashâ€˜ari thought but also solidifies the position of Ilm al-Kalam as a rational and systematic discipline. By critically engaging with various foreign epistemologies, Al-BaghdÄdÄ« not only strengthens Islamic theological arguments but also expands the intellectual horizons of Islamic theology itself.